Genes, Gender, Hormones, and Doping in Sport: A Convoluted Tale - Rogol, Alan D.; Pieper, Lindsay Parks (Frontiers in Endocrinology, 2017)
We are writing this piece in the aftermath of the 2016 Olympic Games in Rio de Janeiro, Brazil. Each of the words in the title plays a role(s) in deciding who may compete, especially who may compete as a woman. Sex verification and anti-doping measures are not new in sport. The sex verification process has gone from inspection of genitalia, to Barr body (chromosome), to genes that determine testicular development, to measuring circulating levels of testosterone to now none of these. Genetic differences are clear among animals, whether single genes or the interactions among multiple genes—some of which may confer sport performance advantages, for example, the erythropoietin receptor, may be neutral, for example complete androgen insensitivity or may confer a disadvantage, for example, some of the genes coding for collagen structure. Those involving hormones are to be clearly distinguished from doping, which implies an exogenous source of drug or a prohibited method, such as blood transfusion. Some athletes with medical conditions have low levels of specific hormones and it is medically recognized that hormone replacement is appropriate. For these athletes a therapeutic use exemption (TUE) is available. It is within this context that pediatric and internal medicine endocrinologists become involved in the diagnosis, treatment and longitudinal care of these athletes.